Սահմանադական զարգացումը Հայաստանի պետականության պայմաններում (առաջին, երկրորդ եվ երրորդ հանրապետությունների ժամանակաշրջանում) - Շուքուրյան, Արմեն (Լիմուշ հրատ.)
В настоящей статье автор подробно проанализировал вопросы развития армянской конституционной мысли и конституции – Современный период на основе трех армянских республиках. Первая Республика в очень сложный политико-правовой период не успела принять конституцию, хотя решение об этом было принято. В советский период было принято три Конституции, которые находились под сильным влиянием Конституции СССР и, по сути, носили декоративный характер. В третьей Республике Армения принята пока только одна конституция, которая дважды подверглась значительным изминениям (в 2005). Конституция РА является более демократической и, по сути, действующей Конституцией. In this article, the author analyzed in detail the issues of the development of the Armenian constitutional thought and constitution – the Modern period based on the three Armenian republics. The First Republic, in a very difficult political and legal period, did not have time to adopt a constitution, although a decision was made to do so. During the Soviet period, three Constitutions were adopted, which were strongly influenced by the Constitution of the USSR and, in fact, were of a decorative nature. In the third Republic of Armenia, only one constitution has been adopted so far, which has undergone significant changes twice (in 2005 and in 2015). Compared to the Soviet constitutions, the RA Constitution is more democratic and, in fact, is an acting Constitution.
Keywords: Իրավունք